Vulnerability of the young university population to HIV/AIDS and other sexually transmitted infections - Junior, Sergio Ferreira; Francisco, Priscila Maria Stolses Bergamo; Loyola, Adriano Mota (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Brazilian universities receive annually thousands of young people who experience situations of vulnerability to the human immunodeficiency virus, sexually transmitted infections, and viral hepatitis. Objective: The aim of the present study was to analyze the secondary data obtained from the attendance record of the rapid testing campaign for these health problems at a federal university in the state of Minas Gerais, Brazil, in 2019. Methods: A cross-sectional study was conducted with secondary data of students (n=1,113) obtained from the standard attendance form by the Ministry of Health during the campaigns Fique Sabendo (Be Aware) in the period between November 25 and 29, 2019. Analyses were performed with the support of the Statistical Package for Social Sciences program, with the calculation of absolute and relative frequencies. Pearson's chi-square test (5%) was used for comparison. Results: The results revealed a young, heterosexual, white profile. More than half reported having consumed alcohol and drugs in their lives. Other findings were the non-use of condoms with steady partners (18.1%) and occasional partners (21.3%), oral sex (86.8%), and unprotected sex in the last intercourse (45.6%). Most declared never being tested for human immunodeficiency virus (74.5%), syphilis (67.4%), hepatitis B (76.1%), or hepatitis C (77.0%). Conclusion: The university population is vulnerable to human immunodeficiency virus and other sexually transmitted infections due to the number of sexual partners and discontinued use of condoms with occasional partners. Such vulnerability is increased by the use of alcohol and other drugs.